Computation and complexity in economic behavior and organization - Mount, Kenneth R.; Reiter, Stanley (Cambridge ; New York : Cambridge University Press, 2002)
This book presents a model of computing and a measure of computational complexity which are intended to facilitate analysis of computations performed by people, machines, or a mixed system of people and machines. The model is designed to apply directly to models of economic theory without requiring analysis of approximations.
Cover; Half-title; Title; Copyright; Dedication; Contents; Acknowledgments; 1 Introduction; 2 F Networks; 3 Networks of Real-Valued Functions; 4 Applications to Economics; 5 Applications to Games; 6 Lower Bounds and Approximations; 7 Organizations; Appendix A Appendix to Chapter 2: Graph Theory; Appendix B Appendix to Chapter 3: Real-Valued Functions; Appendix C Appendix to Chapter 5: Application to Games; Bibliography; Index.
Includes bibliographical references (pages 229-233) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Economics, Mathematical; Organizational behavior; Computational complexity; Comportement organisationnel; Complexité de calcul (Informatique); Mathématiques économiques.; BUSINESS & ECONOMICS -- Economics -- Theory; Computational complexity; Economics, Mathematical; Organizational behavior